2012
DOI: 10.1111/j.1365-2516.2012.02918.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cooling on coagulation and haemostasis: Should “Ice” be part of treatment of acute haemarthrosis in haemophilia?

Abstract: Repeated haemarthroses and the consequences of blood in the joint contribute to blood induced joint disease (BIJD) in people with haemophilia (PWH). Prevention of bleeding, through medical management, is the standard of care in developed countries, but is not universally available due to financial and other barriers. Ice application, as part of R.I.C.E. (Rest, Ice, Compression, Elevation) or alone, is commonly recommended as an adjunct treatment to decrease bleeding, pain, tissue metabolism, oedema, and inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 43 publications
0
30
0
3
Order By: Relevance
“…Cryotherapy could have an immediate reduction of bleeding by vasoconstriction and compression but later lead to cold-induced vasodilatation and interfere with secondary hemostasis. There is also some evidence that application of ice locally impairs hemostasis [7]. This has been seen in humans and in animal models showing prolonged bleeding time, decreased platelet aggregation, increased clotting time, and increased clot formation time [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryotherapy could have an immediate reduction of bleeding by vasoconstriction and compression but later lead to cold-induced vasodilatation and interfere with secondary hemostasis. There is also some evidence that application of ice locally impairs hemostasis [7]. This has been seen in humans and in animal models showing prolonged bleeding time, decreased platelet aggregation, increased clotting time, and increased clot formation time [7].…”
Section: Discussionmentioning
confidence: 99%
“…There is also some evidence that application of ice locally impairs hemostasis [7]. This has been seen in humans and in animal models showing prolonged bleeding time, decreased platelet aggregation, increased clotting time, and increased clot formation time [7]. Hemostasis and coagulation are biochemical reactions that are most efficient at basal body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…We ceased the use of warfarin for 3 days, and her knee was kept at rest and cooled. Rest, ice, compression and elevation (RICE) together or alone is commonly recommended as an adjunct treatment for the treatment of haemarthrosis, to decrease bleeding and pain 9. Haemarthrosis of the knee continued in this patient following this routine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Chesterton also mentioned reducing tissue temperature to <12. 5 C to reduce nerve conduction velocity and to [10][11] C to reduce enzyme activity. 2 It is thought that decreasing intramuscular temperatures by [7][8] C reduces blood flow and metabolic requirements.…”
mentioning
confidence: 99%
“…Indeed, some authors have argued that cryotherapy is not indicated after trauma because cold prolongs bleeding and therefore delays haemostasis, and, furthermore, that blunting inducement of stress proteins may be detrimental to normal tissue repair. 11 Further research is needed to address cryotherapy usage. Future device studies should include placebo groups using pads filled with room-temperature water, both to determine whether there is any role for cryotherapy after deep-tissue injury and to enable blinding of investigators.…”
mentioning
confidence: 99%